Multidisciplinary treatment of complicated coronary root fracture: case report (Research, Society and Development, 2022)
Treatment of trauma to anterior teeth should aim at preserving the affected teeth so as to restore function and esthetic appearance. The management of coronary root fracture is complex and requires a multidisciplinary approach in which various specialties must coordinate to achieve the desired result. This report describes the treatment of a deep crown–root fracture compromising the pulp and extended subgingivally on the buccal aspect. A 57-year-old man presented with pain and mobility in his left maxillary lateral incisor which experienced fall trauma. After using the fractured fragment as a provisional crown, the patient received conventional root canal treatment and a challenger orthodontic extrusion followed by rehabilitation with a postcore- supported prosthetic restoration. A 4-year follow up showed the absence of clinical symptoms and mobility and re-establishment of the periodontal space with satisfactory esthetic results.